2011
DOI: 10.1016/j.jada.2011.06.013
|View full text |Cite
|
Sign up to set email alerts
|

Body Mass Index and Dietary Intake among Head Start Children and Caregivers

Abstract: Background The United States Head Start program serves low-income preschoolers and their caregivers and provides an opportunity for assessment and intervention on obesity. We sought to determine the prevalence of obesity among children and their caregivers and to identify variables that are associated with child BMI z-scores (BMIz) and caregiver BMI. Design/Setting Cross-sectional data on diet and BMI from 770 caregiver-child dyads recruited from 57 Head Start centers in Alabama and Texas. Methods Height a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
1
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 59 publications
2
31
1
1
Order By: Relevance
“…The apparent preference for fruit in Mexican children under age 4 years has also been [11][12][13][14] and Mexican [36] children. In contrast, a higher vegetable intake was observed in Mexican children with adequate body mass index (BMI) compared to those who were obese [36], which is consistent with other studies [31,32]. In our study, larger percentages of children consumed fruit than 100 % fruit juice, which is in line with recommendations to encourage consumption of whole fruit rather than juice and to limit fruit juice intake [16,19].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The apparent preference for fruit in Mexican children under age 4 years has also been [11][12][13][14] and Mexican [36] children. In contrast, a higher vegetable intake was observed in Mexican children with adequate body mass index (BMI) compared to those who were obese [36], which is consistent with other studies [31,32]. In our study, larger percentages of children consumed fruit than 100 % fruit juice, which is in line with recommendations to encourage consumption of whole fruit rather than juice and to limit fruit juice intake [16,19].…”
Section: Discussionsupporting
confidence: 92%
“…These recommendations support optimal growth and development, the establishment of healthy eating habits and the prevention of obesity. Specific feeding practices and dietary factors associated with overweight/obesity in infants and young children such as lack/short duration of breastfeeding [20][21][22][23], early introduction to complementary foods [24][25][26][27], intake of sugar-sweetened beverages [28][29][30], and low fruit and vegetable consumption [31,32], are now recognized to begin in infancy [9], and have been a focus in describing early dietary patterns in infants and young children from national dietary intake surveys in the United States (US) [33].…”
Section: Introductionmentioning
confidence: 99%
“…However, these types of studies lack definite conclusions regarding cause and effect. 46,117,140,[181][182][183][184] On the other hand, while longitudinal studies follow children for a period of time, these types of studies may be limited by the use of retrospective data, parent-based reporting, limited measurements of other covariates, imperfect or missing measurements of confounders, gaps in data reporting, or selection bias. 165,185,186 Crosscomparison studies may prove difficult due to varying study designs and ages of the children.…”
Section: Discussionmentioning
confidence: 99%
“…Aspects of the natural environment are often considered within BE research studies, where they examine accessibility to recreational facilities and schools. 33,94,97,102,116,117 The literature indicates that greenness has many beneficial factors when it comes to influencing childhood obesity and activity levels. In a study that followed 9-10 year olds for 8 years, increased green space was significantly associated with lower BMI z-scores, suggesting that greener neighborhoods led to higher activity levels or more time spent outside.…”
Section: Natural Environmentmentioning
confidence: 99%
“…The current evidence-base on studies evaluating parent-child and parent-ECE center provider communication around nutrition is scarce. Acharya et al (2011), in a cross-sectional study of 770 caregiver-child dyads across 57 childcare centers in Alabama and Texas, reported a positive correlation between the provider and child BMI suggesting the need for ECE centers to be highly engaged in promoting healthy environment for their staff and children. Johnson et al, in a qualitative study of communication between parents and ECE staff about preschoolers’ eating revealed certain barriers to communication including limited time and concerns regarding parent reactions and defensiveness, and a need for ECE staff training around sensitive communication (Johnson et al, 2013).…”
Section: Discussionmentioning
confidence: 99%